Screening of Mungbean (Vigna radiata) Genotypes for Nutrient Stress Tolerance - Hossain, M Altaf (Journal of Agriculture & Rural Development, 2008)
Generally nutrient deficiency of a soil is corrected through application of chemical fertilizers. Fertilizers on one hand are costly and on the other hand it may lead to water pollution by nitrogen and phosphorus from agricultural land. Screening of genotypes for nutrient stress tolerance could be the best alternative to overcome the situation. The present study evaluates the plant growth characters with emphasis on root growth and nutrient uptake of selected mungbean genotypes and examines the efficiency of certain growth parameters for predicting their adaptation in sub-optimal nutrient environment. Some genotypes (VC 6153B, GK3 & VC 6144A) were found to be high nutrient acquiring genotypes and some (PDM 54, IPSA 25 & VO 1443 A-G) were low nutrient acquiring genotypes. Key words: Mungbean, genotypes, nutrient stress.